2018
DOI: 10.2147/jpr.s144220
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic alterations in the excitability of the sciatic and vagus nerves during early stages of sepsis

Abstract: BackgroundNonspecific and delayed diagnosis of neurologic damage contributes to the development of neuropathies in patients with severe sepsis. The present study assessed the electrophysiologic parameters related to the excitability and conductibility of sciatic and vagus nerves during early stages of sepsis.Materials and methodsTwenty-four hours after sepsis induced by cecal ligation and puncture (CLP) model, sciatic and vagus nerves of septic (CLP group) and control (sham group) rats were removed, and select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Previous studies regarding pain and an immune challenge have different results concerning nociception alterations (de Goeij et al, 2013;Diniz et al, 2018;Reeve et al, 2000;Seo et al, 2008). We believe that these diversified data result from the distinct models used (CLP, LPS injection, or cytokine administration), the dose of LPS, the route of administration (intraperitoneally, intravenous, intracerebroventricular) and the time points analyzed (minutes, hours or days after the Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies regarding pain and an immune challenge have different results concerning nociception alterations (de Goeij et al, 2013;Diniz et al, 2018;Reeve et al, 2000;Seo et al, 2008). We believe that these diversified data result from the distinct models used (CLP, LPS injection, or cytokine administration), the dose of LPS, the route of administration (intraperitoneally, intravenous, intracerebroventricular) and the time points analyzed (minutes, hours or days after the Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies regarding pain and systemic inflammation showed that endotoxemia by lipopolysaccharide (LPS) injection could play some role in sensory pain modulation, possible due to its peripheral impairment of sensory neurons (Calil et al, 2014;Hsieh et al, 2018;Meseguer et al, 2014;Ruiz-Miyazawa et al, 2015;Sun et al, 2015). Moreover, in the sciatic nerve was found that the CLP (cecal ligation and puncture) model-induced excitability impairment may enhance mechanical antinociception in the von Frey test (Diniz et al, 2018); although the authors did not state the role of central descending pain modulation in the sepsis model. Leading the same way, Imamura et al (2016) had also shown thermal antinociception on hot plate test in animals with systemic inflammation induced by LPS.…”
Section: Introductionmentioning
confidence: 98%
“…Within 24 h of cecal ligation and puncture (CLP), a model of sepsis, rats display decreased sciatic nerve excitability due to inactivation of sodium channels. 20,55 The electrophysiologic changes occur before notable histologic findings and are associated with higher thresholds for paw withdrawal in response to von Frey filaments. 20 Simultaneously, there is an increase in vagal nerve excitability, which is known to modulate the immune system and have antiinflammatory effects in sepsis.…”
Section: Pain In Rodent Modelsmentioning
confidence: 99%
“…20,55 The electrophysiologic changes occur before notable histologic findings and are associated with higher thresholds for paw withdrawal in response to von Frey filaments. 20 Simultaneously, there is an increase in vagal nerve excitability, which is known to modulate the immune system and have antiinflammatory effects in sepsis. 40,42,85 These findings suggest that pain perception is actually reduced in the early phases after CLP in rats.…”
Section: Pain In Rodent Modelsmentioning
confidence: 99%
“…Before starting the trials, we kept the room at 20-25 °C and gave all rats a few minutes to explore and acclimate to the new environment. The paw withdrawal response is known to be a positive response [16,17]. We used an Electrical Mechanical Analgesia Tester (BME-404, Tianjin, China) to stimulate their operated hind paws with pressure (range: 0 -50 g).…”
Section: Measurement Of the Mechanical Withdrawal Threshold (Mwt)mentioning
confidence: 99%